Readmission for Early Prosthetic Dislocation after Primary Total Hip Arthroplasty - Durand, Wesley M.; Long, William J.; Schwarzkopf, Ran (The Journal of Hip Surgery, 2020)
Prosthetic dislocation in total hip arthroplasty (THA) is the most common cause for readmission in the 90 days following surgery. This investigation sought to quantify risk factors for readmission for early prosthetic dislocation within 30 days after primary THA. This study used the National Surgical Quality Improvement Program (NSQIP) database for the years 2012 to 2017. The primary outcome was reoperation or readmission for prosthetic dislocation within 30 days after primary total hip replacement. Secondary outcomes included native NSQIP medical complications. A total of 159,234 patients were included. Of these, 0.25% (n = 399) experienced reoperation or readmission for prosthetic dislocation within 30 days postoperatively. A total of 217 dislocated hips (54.4%) returned to the operating room only once, and 27 hips (6.8%) returned to the operating room twice. The mean day of first reoperation/readmission for dislocation was 13.5 (standard deviation [SD]: 9.0). In multivariable logistic regression, the following factors were significantly associated with early reoperation/readmission for prosthetic dislocation: patient age 80+ years (odds ratio [OR]: 1.51 vs. 50–59), high creatinine (OR: 1.75 vs. normal range), smoking (OR: 1.53), history of severe chronic obstructive pulmonary disease (COPD) (OR: 1.73), general anesthesia (OR: 1.41 vs. spinal), American Society of Anesthesiologists (ASA) class 3–5 (OR: 1.66 vs. 1 or 2), fracture (OR: 2.17), chronic steroid use (OR: 1.54), and operative duration ≥ 2 hours (all p < 0.05). Early prosthetic dislocation was significantly associated with the further development of surgical site infection (OR: 2.25) (both p < 0.05). This study identified risk factors for early reoperation/readmission for prosthetic dislocation after THA. These findings have implications for preoperative planning, postoperative management, and dislocation precautions.
Keywords: total hip arthroplasty; prosthetic dislocation; NSQIP; complications; risk factors